2002
DOI: 10.1124/mol.61.6.1444
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Preference of G Protein-Coupled Receptor Kinase 3 for the Process of κ-Opioid Receptor Sequestration

Abstract: G protein-coupled receptor kinases (GRKs) phosphorylate opioid receptors, which eventually results in receptor sequestration. With respect to -opioid receptors, it is known that internalization occurs in a species-specific manner. That is, the agonist-occupied human -receptors will sequester whereas murine receptors fail to do so. This investigation concentrates on the internalization of -opioid receptors, employing laser scanning microscopy as a major technique to examine receptor internalization in living ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Similar findings have been reported by other groups using CHO cells, HEK293 cells, or NG108-15 cells expressing the rat or human receptor and U50,488H (Blake et al, 1997b;Jordan et al, 2000;Schulz et al, 2002;McLaughlin et al, 2003). Because pretreatment of the rat and human opioid receptors with U50,488H led to similar levels of AC superactivation, there is no relationship between the degrees of AC superactivation and agonist-induced receptor phosphorylation, desensitization, internalization, and down-regulation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar findings have been reported by other groups using CHO cells, HEK293 cells, or NG108-15 cells expressing the rat or human receptor and U50,488H (Blake et al, 1997b;Jordan et al, 2000;Schulz et al, 2002;McLaughlin et al, 2003). Because pretreatment of the rat and human opioid receptors with U50,488H led to similar levels of AC superactivation, there is no relationship between the degrees of AC superactivation and agonist-induced receptor phosphorylation, desensitization, internalization, and down-regulation.…”
Section: Discussionsupporting
confidence: 71%
“…35 S]GTP␥S binding or inhibition of forskolin-stimulated adenylyl cyclase as the functional endpoint (Blake et al, 1997b;Li et al, 1999Li et al, , 2000Li et al, , 2002Jordan et al, 2000;Schulz et al, 2002;Zhang et al, 2002). In AtT-20 cells or HEK293 cells transfected with the rat receptor-green fluorescence protein, McLaughlin et al (2003) found that the rat receptor was desensitized by 0.1 M U50,488H with agonist-enhanced K ϩ current as the functional endpoint, phosphorylated by 1 M U50,488H, and internalized by 10 M U50,488H.…”
mentioning
confidence: 99%
“…GRK2 primarily targets several GPCRs including ␤-ARs and angiotensin II type 1 receptors, and it is expressed in most tissues. GRK3 targets olfactory receptors, thrombin receptors, kappa-opioid CRF1 (57,219), and ␣1-and ␣2-ARs (12,246). It is found in most tissues, but most prominently in the olfactory epithelium.…”
Section: B Grk Tissue Localizationmentioning
confidence: 99%
“…Using a receptor binding technique, we found that the hkor underwent U50,488H-induced internalization via a GRK-, ␤-arrestin-, and dynamin-dependent process that likely involved clathrincoated vesicles (Li et al, 1999;Zhang et al, 2002). In addition, GRK2 or GRK3 that was co-internalized with the hkor and G protein ␤␥ subunits played a critical role for internalization of the hkor (Schulz et al, 2002). However, unlike U50,488H, etorphine did not promote internalization of the hkor (Li et al, 1999).…”
mentioning
confidence: 99%